Modes effective refractive index difference measurement in few-mode optical fiber - Zhang, Jing (2018)
We studied the measurement and data analysis of modes effective refractive indexes for few-mode optical fiber and found that measuring refractive index difference from the modes interference pattern was affected by dispersion in the optical fiber. A comprehensive method of accurate measurement of modes effective refractive index differences in few-mode optical fiber was developed. It consists of the measurements of the FBG reflection spectrum and the modes interference spectrum, the simulation of interference with dispersion effect in the interferometer configuration, and the data optimization to match with the measured modes interference. The results show much improvement in the few-mode optical fiber characterization.